Glaciation of the central part of the Soer Rondane, Antarctica: glaciological evidence - Pattyn, F.; Decleir, H.; Huybrechts, Philippe (1992)
Ice thickness measurements, carried out by radio echo sounder and gravimeter in the central part of the Sor Rondane Mountains, reveal a subglacial topography of the outlet glaciers and itstributaries characterized by U-shaped valley profiles and overdeepened bedrock. Mass-flux measurements highlight the reduced flow of at least one glacier (Jenningsbreen). This glacier isin the process of being cut off from the main ice supply and may serve as an example for the deglaciation process. An interesting feature of this deglaciation is that, once decoupled from themain ice supply, this glacier is probably characterized by an increased lowering of the ice surface gradient due to the ablation which is characteristic for the upper part of the present outletglacier. In the end this will result in a southward flow of which examples can be found elsewhere in the mountains. On the basis of the field evidence a numerical flow line model ispresented to simulate the behaviour of the outlet glaciers of the central part of the mountains during the last glacial maximum. These experiments show an increase of 300-400 m in icethickness under realistic assumptions for mass balance, temperature and sea level. Some of the higher glacial levels are then attributed to an environment characterized by a higheraccumulation predating the last glacial maximum.